Novel high protein-energy balls formulated with date paste enriched with Samh seeds powder and/or different milk protein origins: effect on protein digestibility in vitro and glycemic response in young adults - Alsuhebani, Hathami; Sakr, Sally S.; Elkashef, Hany; Algheshairy, Reham M.; Alfheeaid, Hani A.; Algeffari, Metab; Alharbi, Hend F. (Frontiers in Nutrition, 2025)
ObjectivesThe rising demand for convenient and nutritious food options, especially among young adults with fast-paced lifestyles, highlights the need for quick energy and protein sources during physical activities and breakfast. Consequently, aimed to formulate and evaluate the nutritional, functional, and glycemic properties of high-protein energy balls using Sukkari date paste a variety of the date palm (Phoenix dactylifera L.) paste, Samh seed (Mesembryanthemum forsskalei Hochst) powder, whey protein concentrate, and camel milk powder.MethodsThe nutritional value of the formulated balls was evaluated by assessing their chemical composition, dietary fibers, amino acids (AAs), and fatty acids (FAs). Additionally, antioxidant properties were determined using the DPPH method and reducing power assays. In vitro protein digestibility was also measured. Furthermore, the in vitro glycemic index and glycemic load, as well as the human glycemic response for various samples, were examined.ResultsSamples containing combinations of date paste, Samh seeds, and either camel milk powder (DSC) or whey protein concentrate (DSW) demonstrated high nutritional value, with significant caloric content measured at 352.76 ± 0.125 Kcal/100 g for the first combination and 328.76 ± 0.242 Kcal/100 g for the second. These samples also showed significant (p < 0.05) DPPH radical scavenging activity, with values of 63.78 ± 2.43 μg of ascorbic acid equivalent/g for the date paste and Samh seeds with camel milk powder (DSC) and 59.87 ± 2.61 μg of ascorbic acid equivalent/g for those with whey protein (DSW). Furthermore, the presence of a variety of essential amino acids and fatty acids in DSC and DSW was higher than in the rest of the samples (DS, DW and DC), which is under the current study. Sensory evaluations indicated that all samples were highly accepted. The in vitro study revealed that the degree of protein digestibility was higher in samples that contained both Samh seeds powder and whey protein concentrate or camel milk powder than in the sample that contained Samh alone. Also, all samples exhibited low in vitro glycemic index (<55) and glycemic load (<10). Moreover, the human glycemic response evaluation showed that blood glucose levels gradually declined after 30 min, returning to pre-meal levels by 120 min, indicating no post-meal hyperglycemia, resulting in a normal glycemic response in healthy young adults.ConclusionsCombining Samh seed powder with dairy proteins to create protein-energy balls using Sukkari date paste results in nutritious snacks that are rich in amino acids, fatty acids, dietary fibers, and antioxidant compounds. These snacks also have a low glycemic response and high protein digestibility in vitro. Therefore, high-protein energy balls made from date paste enriched with Samh seed powder, along with either camel milk or whey protein powders, are recommended as a protein and energy source for healthy young adults who do not experience post-meal hyperglycemia.